Expression Level of HIV-1 Vif Can Be Fluctuated by Natural Nucleotide Variations in the vif-Coding and Regulatory SA1D2prox Sequences of the Proviral Genome - Doi, Naoya; Koma, Takaaki; Adachi, Akio; Nomaguchi, Masako (Frontiers in Microbiology, 2019)
Vif is required for HIV-1 replication in natural target cells by counteracting host restriction factors, APOBEC3 (A3) proteins. We recently have demonstrated that the expression level of Vif protein can be changed by naturally-occurring single-nucleotide variations within SA1D2prox located at the central region of viral genome. We also have found that the levels for vif and vpr mRNAs are inversely correlated. While the amino acid sequence per se is critical for Vif functionality, its expression level modulated by signal sequences in its coding region is likely to be important as well. There are two such sites in the region that are involved in the vpr expression. To reveal possible fluctuations of Vif-expression level, we examined the SA1D2prox region and vif gene by chimeric approaches using HIV-1 subtypes B and C, which exhibit distinct anti-A3 activity. In this report, recombinant clones in the subtype B backbone that carry chimeric sequences with respect to SA1D2prox/vif and those within the vif-coding region were generated. Of these, clones that have the vif-coding sequence of subtype C, especially its 3’ region, expressed vif and Vif at a decreased level but did at an increased level for vpr and Vpr. Clones with reduced vif level grew similarly or slightly better than a parental clone in a weakly A3G-positive cell line but more poorly in a highly A3G-expressing cell line. Taken all together, our results show that natural variations in the SA1D2prox and vif-coding region can change the Vif-expression level, thereby affecting the HIV-1 replication potential.